INCREASED READING SKILLS ALOUD USING MODELING STRATEGIES IN GRADE II STUDENTS OF SDN 009 SANGATA UTARA - Syahdinar, Elsy; Ridhani, Ahmad; Sili, Surya (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
The purpose of this research is ti find out the results of the use of modeling grade in SDN 009 Northen Sangatta. Specially for the improvement of reading aloud in the pre reading stage when reading the post reading stage with the modelling strategies of of second grade elementary school student 009 Northen Sangatta. This research methodology is a type of classroom action research, research procedures used are planning, action, observation, and reflection. This research uses three cycles one cycle twice meeting. The problems contained in the first cycle will be followed up by the second cycle research and the third cycle research.The results of this study are the ability of pre reading in the first cycle an average of 60,7 % , the twice cycle an average of 73,2 % and an average the third cycle of 81,8 %.Â  The ability to read aloud from the pre cycle test value which is used as the basic value obtained before the average action of 64,4 with sufficiently improved criteria in the first cycle of action of an average of 67,5 with sufficient criteria, increased cycle two by an average of 69,8 with the criteria are sufficient and increase in the average three cycle of 75,4 with good criteria. Post reading ability in cycle one is 64,2 % an average cycle two is 69,8 % and cycle three is 81,8 %. The conclusion that the application of modeling strategies can increase the ability to read aloud preweens when reading and post reading of second grade elementary school student 009 Northen Sangatta.